Formação continuada na rede municipal de ensino de Chapecó: um tecido a ser cerzido - Badin, Ana Maria Andreola (2017)
In this study, we tried to delineate, as far as possible, the trajectory on Continuing Education in the Municipal School of Chapecó Education, from 1994 to 2015, whose title is complemented by the following terms: a fabric to be darkened. The research analyzed the municipal and national legislations related to this theme, as well as the publications and some documents found in the Education Department of the municipality and some private collections. The central issue that triggered and led many of the reflections turned around the search for understanding and historization about how the process of continuing education in the municipal teaching network of Chapecó occurred. For this, we start from the initial hypothesis that a great part of the difficulty of articulation between the theoretical themes and the daily school practice could be associated to a possible thematic instability. We consider the ideas of some theorists to base our reflections, namely: Saviani (2008-2013), Gatti (2008- 2011), Davis (2012), Nóvoa (2010) and Brzezinski (2008). This choice was due to the fact that, because it is a documentary research, we prioritize focusing on the structure of the educational process of this educational context, considering the necessary care and attention to this challenge. It was a documentary and bibliographic research based on Sá-Silva (2009), and also based as a methodological axis in Hermeneutics of Depth (HP) proposed by Thompson (1995) articulated with the Content Analysis proposed by Bardin (2004) . The analysis of the documents made it possible to establish a chronological line of events that allowed us to recover important moments in the structuring of the continuing education in the municipal education network of Chapecó. Some considerations were possible to be observed, among them, that of our initial hypothesis, since we evidenced that the model of continuous formation seems to be unstable with respect to its thematic proposals, in the sense of not allowing a deepening and highlighted the lack of the teachers involved voice. These notes were also evidenced in other studies and educational contexts, supporting our learning on the same theme.